Grant F. Walton (1924-1988) - Tedrow, J.C.F. (ARCTIC, 1988)
Grant F. Walton, Professor Emeritus, Rutgers University, died on August 4, 1988. . While pursuing his Ph.D. degree at Rutgers University he wrote his thesis on soils of the High Arctic. Accordingly, he made studies in Alaska, Prince Patrick Island, Bathurst Island, Cornwallis Island, Banks Island, Baffin Island, the Hudson Bay area, northern Greenland and Siberia. His Ph.D. thesis was a comprehensive (480 pages) circumpolar treatment of soil zonation and soil geography in the High Arctic. He was particularly interested in the effect of glaciation and isostatic rebound on the soil pattern. It became evident to the university during the late 1960s and early 1970s that Dr. Walton also had considerable organizational and administrative talents. [He served as dean of Cook College and director of the New Jersey Agricultural Experiment Station, a dual post he held for eight years.] . When he retired in 1987 he held the title of Professor II (Distinguished Professor). .